The Grey-Based Taguchi Method: Optimization of Milling of Mold Steel - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2018)
In this study, surface roughness and cutting forces were experimentally investigated in a PMD 23 cold work tool steel milled with multi-layer Al2O3+TiCN coated cutting tools. The effects of progress rate, cutting speed and cutting depth on surface roughness and cutting forces were investigated. The Taguchi technique was used to optimize the milling process. With this study, optimal machinability of PMD 23 cold work tool steel with multi-layer Al2O3+TiCN coated tools was determined by Taguchi Grey based optimization technique. The optimum value is obtained by Taguchi based Grey relational analysis when the machining parameters are as follows: 500 mm/min feed, 3500 rpm spindle speed and 1.0 mm cutting depth (A1B3C2).
Keywords: STAINLESS-STEEL; MACHINING PARAMETERS; SURFACE-ROUGHNESS; TOOL PERFORMANCE; END; MACHINABILITY; WEAR; LIFE